SCIENTIFIC COLLABORATION NETWORKS IN BIOSYSTEMS ENGINEERING IN BRAZIL - da Silva, C. E. M. V; Nunes, R. (Revista Brasileira de Engenharia de Biossistemas, 2016)
Among other engineering specialties, the Biosystems Engineering is one that is still in process of been molded, in Brazil as well as abroad. In the Brazilian case there is a few number of academic research/ teaching institutions that get together communities of professors/ researchers occupied with Biosystems Engineering. To determine how this molding is in progress, the Social Network Analysis techniques were applied to some of these communities. With this purpose the Curriculum Vitae (CV Lattes, CNPq) of the researchers were utilized to determine the coauthoring partnership into the production of scientific papers among each of the analyzed community. As a result it was found among the leading researchers a remarkable diversity of field of interest, and a low grade of internal collaboration, internal to each studied community.